Comomentum: Inferring Arbitrage Activity from Return Correlations. (27th October 2021) - Lou, Dong; Polk, Christopher
Abstract: We propose a novel measure of arbitrage activity to examine whether arbitrageurs can have a destabilizing effect on the stock market. We focus on stock price momentum, a classic example of a positive-feedback strategy that our theory predicts can be destabilizing. Our measure, dubbed comomentum, is the high-frequency abnormal return correlation among stocks on which a typical momentum strategy would speculate. When comomentum is low, momentum strategies are stabilizing, reflecting an underreaction phenomenon that arbitrageurs correct. When comomentum is high, the returns on momentum stocks strongly revert, reflecting prior overreaction from crowded momentum trading that pushes prices away from fundamentals. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.